2012
DOI: 10.1002/j.2161-1882.2012.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Promoting Resilience: An Additional Tool to Address the Increasing Number of College Students With Psychological Problems

Abstract: This study examined the assessment of resilience in undergraduate college students. Multigroup comparisons of the Connor–Davidson Resilience Scale (CD‐RISC; Connor & Davidson, 2003) were performed on general population students and students recruited from campus mental health offices offering college counseling, psychiatric‐support, and disability‐support services. Results found that the 10‐item CD‐RISC demonstrated strong fit and reliability, with significantly higher scores for general population students. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 45 publications
5
44
2
2
Order By: Relevance
“…The mean and median resilience score was 24 out of a possible 40 (a recent study reported an average resilience score of 30 for U.S. youth populations) [27]. Twenty-seven per cent of participants reported eating fast food three or more times in the past week, 24% reported doing no exercise in the past week, and 79% had not visited a health professional for more than one year.…”
Section: Resultsmentioning
confidence: 99%
“…The mean and median resilience score was 24 out of a possible 40 (a recent study reported an average resilience score of 30 for U.S. youth populations) [27]. Twenty-seven per cent of participants reported eating fast food three or more times in the past week, 24% reported doing no exercise in the past week, and 79% had not visited a health professional for more than one year.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the demographic shifts within the college student population, discussed throughout this review also include increasing diversity in terms of types and incidence of psychological problems among the college student population (Hartley, 2012;Kitzrow, 2003). The population of people who are of traditional age for college attendance displays high rates of psychological disorders whether they are enrolled in college or not (Hayes, Soo Jeong, Castonguay, Locke, McAleavey, & Nordberg, 2011).…”
Section: Most Common Psychological Problems For College Studentsmentioning
confidence: 99%
“…The population of people who are of traditional age for college attendance displays high rates of psychological disorders whether they are enrolled in college or not (Hayes, Soo Jeong, Castonguay, Locke, McAleavey, & Nordberg, 2011). In addition, given that the most common psychological problem faced by college students stems from psychological stress, research has focused on developing validated tools for college counselors to help students reduce stress and increase resilience (Hartley, 2012).…”
Section: Most Common Psychological Problems For College Studentsmentioning
confidence: 99%
See 2 more Smart Citations